AN APPLICATION OF CHORAL READING STRATEGY IN ENGLISH LANGUAGE LESSONS IN ECONOMIC TEXT TO INCREASING READING SKILLS FOR THE STUDENT GRADE XI STATE VOCATIONAL SCHOOL 2 MEDAN - Nasution, Sarah; Zulkarnain, Mierna; Suhariyanti, Suhariyanti (Universitas Dharmawangsa Medan, 2020)
The objectives of this study are: (1) to determine the application of Choral Reading learning strategies relating to texts relating to Economics in learning English; (2) to determine the effectiveness of the application of choral reading learning strategies in English learning to students' reading skills. This type of research is Classroom Action Research which consists of two cycles. Subjects in the study were students of class XI with a total of 30 students. Data collection techniques that will be used are observation, documentation, and testing. The qualitative data analysis technique is by doing reflection notes, the thoughts that arise when observing, and are the results of the process of comparing, linking, or linking the data displayed with previous data. The results of this class action research showed an increase in initial ability compared to cycle 1, namely students who completed in cycle 1 numbered 15 students or 50.00%. From the results of the second cycle, it can be written that students who have completed are 24 students from 30 students or 80.00%. From cycle 1 to cycle 2 there was a 30% increase. This proves that the use of Choral Reading learning strategies is very effective.